Family Belief System and Infidelity in Cohabiting Couples in Tarapoto - Rojas Ramón, Ruth Nora (2023)
This article analyzes and explains the link between the family belief system and infidelity in cohabiting couple who receive assistance in a public institution in Tarapoto – Perú. The objective of the study was to explore and publicize the influence of family belief systems on infidelity behaviors. This study was carried out using the qualitative method. The analysis of the results of the individual in-depth interviews with both members of the couple was framed in a systemic approach. From the investigation, it was obtained that there are similarities between the members of the couple regarding their beliefs, which generates a greater tolerance towards unfaithful male behavior. In other words, there is an affinity in the beliefs of men and women about: gender roles, love family, biological differences between men and women among others. Personal, family y social beliefs are deep-rooted and are hardly questioned, but tend to be reinforced. In t[his sense, the research allowed  to approach a better understanding of the relationship between the belief system and unfaithful behavior, both in men and women. This study will help to gain an in-depth understanding of this psychosocial reality, which affects people is psychological well-being.